2015
DOI: 10.4103/1596-3519.149877
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of cognitive impairment in patients with chronic kidney disease: A cross-sectional study in Benin City, Nigeria

Abstract: CKD is associated with significant CI in Nigerian patients especially with progressive deterioration in renal function. There is a need for regular evaluation of CKD patients for cognitive deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 27 publications
3
28
0
2
Order By: Relevance
“…These authors explained that high risk of cardiovascular and cerebrovascular diseases can increase risk cognitive impairment in patients with impaired kidney function [6][7][8][9][10][11]. Additionally, many conditions such as anemia, hypoproteinemia, and oxidative stress, may link CKD with reduced cognitive function [12,13]. Furthermore, accumulative evidence has also demonstrated that the association remains unchanged even after controlling for cardiovascular and cerebrovascular diseases, suggesting that reduced kidney function may be an independent risk factor for cognitive impairment, although their mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These authors explained that high risk of cardiovascular and cerebrovascular diseases can increase risk cognitive impairment in patients with impaired kidney function [6][7][8][9][10][11]. Additionally, many conditions such as anemia, hypoproteinemia, and oxidative stress, may link CKD with reduced cognitive function [12,13]. Furthermore, accumulative evidence has also demonstrated that the association remains unchanged even after controlling for cardiovascular and cerebrovascular diseases, suggesting that reduced kidney function may be an independent risk factor for cognitive impairment, although their mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A graded relationship has been found between eGFR and cognition, with each 10 ml/min per 1.73 m 2 decline in eGFR being associated with 11% higher prevalence of cognitive impairment (14). Few studies have evaluated the risk conferred by low serum bicarbonate on cognitive function, with mixed results (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…[1] This study was designed with the aim to determine the prevalence and the find out the determinants of cognitive impairment among CKD patients in Nigeria. The authors, at the end of the study, conclude that the CKD is associated with significant cord injury in Nigerian patients, especially with progressive deterioration in renal function.…”
mentioning
confidence: 99%
“…The authors, at the end of the study, conclude that the CKD is associated with significant cord injury in Nigerian patients, especially with progressive deterioration in renal function. [1] Authors deserve appreciation for their effort. However, I have some concerns with this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation